Knowledge, Attitude, and Beliefs of Communities and Health Staff about Echinococcus granulosus Infection in Selected Pastoral and Agropastoral Regions of Uganda. (13th May 2018) - Othieno, Emmanuel; Ocaido, Michael; Mupere, Ezekiel; Omadang, Leonard; Oba, Peter; Okwi, Andrew Livex
Abstract : A descriptive cross-sectional survey was done to determine knowledge, attitudes, and beliefs of the communities and health workers about cystic echinococcosis (CE) in pastoral region of Northeastern (NE) and agropastoral regions of Eastern (E) and Central (C) Uganda. Overall a total of 1310 participants were interviewed. Community respondents from NE region were more aware of CE infection than those from Eastern (OR 4.85; CI: 3.60–6.60;p < 0.001 ) and Central (OR 5.73; CI: 4.22–7.82;p < 0.001 ) regions. 19.8% of the respondents from EA region had positive attitude towards visiting witch doctors for treatment compared with 62.0% and 60.4% from NE and Central regions, respectively (p < 0.001 ). Notably, the awareness of CE increased with level of education (p < 0.001 ). There was no statistical difference between male and female respondents as far as awareness of CE was concerned (p > 0.05 ). 51.7% of the community respondents from Central believed CE is caused by witchcraft, compared with 31.3% and 14.3% from NE and EA regions, respectively (p < 0.001 ). There was no statistical difference between health staff regarding their knowledge, attitude, and beliefs about CE infection (p > 0.05 ). None of the participants knew his/her CE status. The communities need to be sensitized about CE detection, control, and management and health staff need to be trained on CE diagnosis.